STRATEGI PENGEMBANGAN AGROINDUSTRI NATA DE COCO DI KABUPATEN INDRAGIRI HILIR - Evy Maharani; Susy Edwina; Yeni Kusumawaty (Indonesian Journal of Agricultural Economics, 2010)
The potential of coconut as one of economical agriculture commodities that can be processedinto products such as nata de coco and others. This survey study was conducted in Tembilahan,Indragiri Hilir District as an area which has the nata de coco agroindustry. This research wasconducted from May to August 2008. The results concluded that development strategies for natade coco indsutry are as follow: improve production planning capability, increase productioncapacity, improve the standard of product quality, enhance marketing campaigns through widerdistribution, diversify market segments and use institutions such as Aspari.